Enhancing Reading Skills through Visualizing Strategies: A Fresh Approach for English Education Students at Kuningan University - Thamrin, Nani Ronsani; Darmawan, Erlan; Irawan, Dede (Jurnal Pendidikan Bahasa Inggris undiksha, 2025)
Reading comprehension remains a challenge for many English as a Foreign Language (EFL) students, particularly in engaging with and understanding texts effectively. Traditional teaching methods often fail to encourage active participation and critical thinking, resulting in low motivation and limited comprehension skills. To address this gap, this study investigates the implementation of visualizing strategies to enhance reading comprehension skills among English Education students at Universitas Kuningan. Visualizing strategies encourage students to create mental images of the text, fostering deeper engagement and understanding of the material. The research employed a qualitative approach within a collaborative action research (CAR) framework, involving 14 students as participants. Data collection methods included classroom observations, student reflections, and pre-and post-test assessments of reading comprehension. The findings indicate that integrating visualizing strategies into reading instruction significantly improved students' comprehension of folktale texts. Students demonstrated enhanced abilities to identify main ideas, draw cultural connections, and confidently articulate their understanding through discussions and retelling activities. The pre-test average score of 59.4 increased to 85.7 in the post-test, with all students exceeding the Minimum Mastery Criterion (MMC) of 75. Participants also reported increased motivation and enjoyment, attributing their progress to the strategy's interactive and engaging nature. This study recommends a broader application of visualizing strategies in English language education to support comprehension and engagement across diverse text genres. Further research is suggested to explore its adaptability and impact in different educational contexts..